Avaliação da influência de parâmetros físico-químicos na concentração de composto químico em snack frito: emprego de ferramentas quimiométricas e estatística - Ragazi, Gabriel Bernardes Cabreira (Universidade Federal de São Carlos, 2021)
PepsiCo presents an extensive product portfolio, and it is one of the world's leading food companies. Among its segments, the Salty Snacks category is one of the most important to the company, featuring global brands such as Lays, Cheetos, Ruffles and Doritos. Snacks are a popular form of meal among consumers and provide convenience, besides they are easily accessible and satisfy short-term hunger. Therefore, they meet the demand of the urbanized world where agility has been increasingly desired. The consolidation of PepsiCo in the market comes from several factors, one of them is the guarantee of always offering a quality product. Therefore, the company always seeks to understand how each parameter and characteristic of the raw materials used in the production process can impact the products that the consumers will receive. In this thesis, it was evaluated the correlation of total solids content with the concentrations of a certain chemical compound (confidential) in a fried snack. In addition, different parts of the chip of this snack were evaluated to verify in which of them the concentration of the chemical compound was more pronounced. The use of chemometrics in this evaluation allowed the observation of the effects of variables and interactions between them, being important to understand the processes that were being monitored. With the use of statistical and chemometric tools, such as t test, Tukey test and PCA, it could be verified that higher levels of total solids in the studied raw material tend to present a higher concentration of the chemical compound X in the fried snack, while the part A (extremities) of the chip has a higher concentration of the compound. In addition, part A is significantly different from the other studied parts (B, C and D), both when the raw material has high and low total solids. As parts B, C and D do not show significant difference between them, considering that part D represents the entire chip, it could be observed that even part A presenting high concentrations of compound X, its impact is not significant on the final product.
Evaluation of the influence of physicochemical parameters on the concentration of a chemical compound in fried snack: use of chemometric and statistical tools
Keywords: Planejamento fatorial; Alimentos; Qualidade; Testes de significância; Análise de Componentes Principais; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ANALISE DE TRACOS E QUIMICA AMBIENTAL